A QIP aimed at improving the recording of patients with discharge bodyweight of heart failure in the acute cardiac unit - Minesh Patel; Chie Katsura (Future Healthcare Journal)
Introduction: Diuretic therapy has an important role in the management of fluid overload in patients with decompensated heart failure (HF). Further to this, having a previous dry weight available aids cardiologists and community heart failure nurses in optimising diuretic therapy during readmissions and in their HF follow-up in the community. This information was not readily available on the computer systems at the acute cardiac unit (ACU). Therefore, a project was devised with an aim to record the dry weights of patients in discharge letters to promote awareness and reporting. This project was supervised by a consultant cardiologist and the hospital’s heart failure nurse was involved. A baseline audit had shown that only eight discharge letters out of 85 (9.4%) for patients with HF included a dry body weight. Material and methods: Two interventions were implemented to promote the reporting of dry weights in discharge letters. The first (plan–do–study–act (PDSA) 1) was to draft and distribute a cardiology induction handbook with an excerpt highlighting the need for dry weight recording in discharge letters for newly rotating resident doctors in the ACU in December. The second intervention (PDSA 2) consisted of an in-person presentation to the newly rotating resident doctors in April. All discharge letters for patients with HF were examined for compliance throughout the duration of the project. Results and discussion: Following PSDA 1, 25% of discharge letters included a dry body weight. Subsequently, in the period after PDSA 2, this increased to 38%. In all, there was an overall improvement in reporting. Conclusion: To conclude, we report that the proportion of discharge letters with recorded dry body weights had risen to above 35% following our quality improvement project. Overall, the community HF nurses found this work useful in the follow-up of their patients. Additional methods of distributing dry bodyweights in patients with HF could be to include these in clinic letters in the future.